Solutions of the equation x2-(p2 q2 ± ap)y2=kt - Chandoul, Amara; Sibih, Alanod (Edelweiss Applied Science and Technology, 2024)
In this note, the Diophantine equation x2-(p2 q2 ± ap)y2=kt has been solved, and its positive integer solutions have been stated in terms of generalized Fibonacci, generalized Lucas, generalized Pell, and generalized Pell-Lucas sequences. We have discovered units for Z[D] in terms of the above sequences of numbers.